A new species of Roseodiscus (Ascomycota, Fungi) from tropical China - Zheng, Huan-Di; Zhuang, Wen-Ying (Phytotaxa, 2013)
A new species, Roseodiscus sinicus is described and illustrated. The fungus, collected on stems of an unknown monocotyledon, is characterized by dirty white apothecia, large and thin-walled ectal excipulum cells, Calycina-type ascus apical ring, and ellipsoid, multiguttulate ascospores. The placement of the new species in Roseodiscus was also supported by ITS rDNA sequence analysis. The distinctions between the new species and related taxa are discussed.